2001
DOI: 10.1111/j.1469-7793.2001.0349f.x
|View full text |Cite
|
Sign up to set email alerts
|

External K+ relieves the block but not the gating shift caused by Zn2+ in human Kv1.5 potassium channels

Abstract: Changing the extracellular concentration of divalent cations can have dramatic effects on the behaviour of electrically excitable membranes as illustrated by the lowering or raising of the threshold for cell firing caused by hypo-or hypercalcaemia, respectively (Frankenhaeuser & Hodgkin, 1957). Voltage-clamp analyses have shown that the divalent cation-induced change of excitability can be linked to a shift of the voltage dependence of channel gating. For example, an elevation of the external concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 27 publications
4
36
0
Order By: Relevance
“…The most common effect of extracellular Zn 2ϩ is allosteric modulation, potentiating or inhibiting channel activity (32,33). Examples are numerous, including K V (34,35), Na V (36,37), Ca V (38,39), ionotropic receptors for ␥-aminobutyric acid (40,41), glycine (42), 5-hydroxytryptamine (43), glutamate (44,45) and ATP (46 -48), two-pore K ϩ channels (49,50), acid-sensitive ion channels and epithelial Na ϩ channels (51,52), and TRPM1 channel (53).…”
mentioning
confidence: 99%
“…The most common effect of extracellular Zn 2ϩ is allosteric modulation, potentiating or inhibiting channel activity (32,33). Examples are numerous, including K V (34,35), Na V (36,37), Ca V (38,39), ionotropic receptors for ␥-aminobutyric acid (40,41), glycine (42), 5-hydroxytryptamine (43), glutamate (44,45) and ATP (46 -48), two-pore K ϩ channels (49,50), acid-sensitive ion channels and epithelial Na ϩ channels (51,52), and TRPM1 channel (53).…”
mentioning
confidence: 99%
“…Inhibition of WT Kv1.5 by H ϩ or Zn 2ϩ is antagonized either by raising [K ϩ ] o or by the R487V mutation (25,51). Similarly, the [K ϩ ] o dependence of Kv1.5 H463G currents is mitigated by the R487V mutation as implied in Fig.…”
Section: Mtset and Mtses Irreversibly Inhibit Currents Of Cysteinesubmentioning
confidence: 74%
“…The molecular determinants of these binding sites are unknown. Recent studies of Kv1.5 channels have shown that Zn 2ϩ may act on two distinct binding sites, one of which is located within the pore turret (32,67,68). It is possible that at least one Zn 2ϩ binding site is also located within the pore turret of the Kv1.4-1.1 channel, since the amino acid sequence of this region is similar to that of the Kv1.5 channel.…”
Section: Discussionmentioning
confidence: 99%